Functional Cortical and Cerebellar Reorganization in a Case of Moyamoya Disease - Calabrò, Rocco S. (Innov Clin Neurosci, 2015)
Background: Functional studies have been previous reported in stroke patients, but no studies of functional magnetic resonance imaging have been performed in Moyamoya disease. Objective: To assess the cortical and cerebellar reorganization in a moyamoya patient. Methods: We reported a case of a patient suffering from moyamoya disease, undergoing a neuropsychological assessment, a neurocognitive rehabilitative treatment, an electroencephalogram evaluation, and a functional magnetic resonance imaging examination. Results: The subject showed a cognitive impairment, a slow electroencephalogram activity, and the ipsi- and controlateral motor cortex and cerebellar functional magnetic resonance imaging activation. Conclusions: This is the first functional magnetic resonance imaging case study reported in moyamoya disease. We showed a cortical reorganization, which could play an important role in clinical evaluation and motor recovery. The cerebellar activation, showed after cognitive and motor rehabilitation, could support the idea that the cerebellum contains several cognitive-related subregions involved in different functional networks in moyamoya disease.